Free movement and quality of agri-food products in Europe: summary of the debates (Club de Bruxelles BrussellesBE, 1992)
Summaries of the debates in the following topics - the policy on food quality in the framework of the Common Agricultural Policy; how can the distinct characteristics of regional products be protected and fostered (designations of origin, geographical indicators, labels)?; how should national legislation be harmonised and what forms of standardisation should apply to agri-food products in the Single Market?; and can health and veterinary regulations form a barrier to the free movement of certain products? Can technology contribute to the higher quality now sought by the catering trade and some consumers?
DC